Legal Reforms for Preventing Employer Abuse: Crafting a Socially Just Employment Law Framework - Hari Triasmono; Yovita Arie Mangesti; Ferry Irawan Febriansyah; Richard Tomlins; Nazli Bin Ismail Nawang (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
This research aims to examine the role of employment law in overcoming the challenges of abuse of power by employers to build a legal framework that is socially just. This challenge is in focus because of its impact on imbalances in employment and labour relations. In this context, labour law has an important role in protecting workers' rights and preventing abuse of power by employers in the corridor of legal reform that provides social justice. The research method used is a normative legal approach. Through analysis of various legal regulations, court decisions, and related literature, this research seeks a comprehensive understanding of the concept of employment law and its relevance in overcoming the challenges faced. The novelty of this research lies in its holistic approach, integrating social justice, proactive prevention, technology use, and worker participation in employment law reforms to prevent employer abuse, ensuring comprehensive and fair protection for all workers. The research results show that labour law plays a crucial role in ensuring social justice in the work environment and in carrying out legal reforms. Clear regulations and effective law enforcement are key to preventing abuse of power by employers and protecting workers' rights. Thus, labour law is not only an instrument of protection but also a foundation for building a legal framework that is socially just. In conclusion, comprehensive labor law implementation and collaboration among government, employers, and workers are essential for creating a fairer and more socially just work environment.